2017
DOI: 10.1101/148544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective maintenance of multiple CRISPR arrays across prokaryotes

Abstract: Prokaryotes are under nearly constant attack by viral pathogens. To protect against this threat of infection, bacteria and archaea have evolved a wide array of defense mechanisms, singly and in combination. While immune diversity in a single organism likely reduces the chance of pathogen evolutionary escape, it remains puzzling why many prokaryotes also have multiple, seemingly redundant, copies of the same type of immune system. Here, we focus on the highly flexible CRISPR adaptive immune system, which is pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…8 assumed an exponential decay in expression of leader-distant spacers; both found that a repertoire of five to seven spacers is sufficient to optimize immunity. However, actual CRISPR repertoires consist of many more spacers (2, 7-9) distributed across multiple cassettes (5), with many dozens of spacers translated into RNA in a sporadic manner across each cassette despite a gradual decay in expression from the leader end (12)(13)(14). Thus, we pursued the alternative hypothesis that the primary role of CRISPR is to retain a long-term memory of previous invasions to guard against the diverse landscape of phage species (15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 assumed an exponential decay in expression of leader-distant spacers; both found that a repertoire of five to seven spacers is sufficient to optimize immunity. However, actual CRISPR repertoires consist of many more spacers (2, 7-9) distributed across multiple cassettes (5), with many dozens of spacers translated into RNA in a sporadic manner across each cassette despite a gradual decay in expression from the leader end (12)(13)(14). Thus, we pursued the alternative hypothesis that the primary role of CRISPR is to retain a long-term memory of previous invasions to guard against the diverse landscape of phage species (15).…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR-Cas mechanism for immunity has three stages (2,3). Following a first encounter with a virus, after a successful defense through another mechanism or if the virus is ineffective for some reason (4), some of the Cas proteins recruit pieces of viral DNA and integrate these spacers into an array separated by palindromic repeated sequences in one of several CRISPR loci (5) of the bacterial genome. Each array defines a CRISPR cassette, and together, the cassettes carry a memory of past infections.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, our understanding of the ecological and evolutionary consequences of CRISPR-Cas immune responses are limited to in vitro experiments that lack much of the biotic and abiotic complexity of natural environments. Could it be that the biotic and abiotic complexity of the real world, where communities of microbes include multiple species and strains as well as diversity in phage and plasmids, are spatially structured and exist in fluctuating environments are critical to the evolution and maintenance of CRISPR (50,85,139,140)? Filling these gaps in our current understanding of CRISPR ecology and evolution requires interdisciplinary approaches that combine observational studies, mathematical and computer simulation models, as well as population and evolutionary dynamics experiments.…”
Section: Discussionmentioning
confidence: 99%